Circadian alignment as a modifiable target in adolescent mental health: mechanisms and preventive approaches - Staszko, Natalia; Bała , Kamila; Zbroniec, Jakub; Bukowska, Małgorzata; Biskup, Alicja; Smagowska, Julia (Journal of Education, Health and Sport, 2026)
Adolescence is a developmental period characterized by a physiologically delayed circadian phase and ongoing maturation of neural systems involved in emotional regulation and cognitive control. This developmental configuration increases susceptibility to sleep restriction and circadian misalignment, particularly in the context of contemporary lifestyle patterns marked by high evening screen exposure. Short-wavelength light emitted by electronic devices has been linked to delayed sleep timing and social jetlag, which are common among adolescents.This narrative review synthesizes current evidence on the relationships between circadian rhythm disruption, sleep disturbances and mental health outcomes in adolescents. Particular attention is given to biological mechanisms potentially underlying these associations, including alterations in melatonin signaling, dysregulation of monoaminergic neurotransmission, activation of the hypothalamic-pituitary-adrenal axis, inflammatory pathways and interactions within the gut-brain axis. The review also examines the cognitive and academic correlates of insufficient and irregular sleep during this critical developmental stage. Emerging evidence indicates that circadian misalignment and chronic sleep restriction are consistently associated with depressive and anxiety symptoms, emotional dysregulation and reduced cognitive performance in adolescents. Circadian-oriented strategies, such as reducing evening light exposure, delaying school start times and implementing structured sleep hygiene programs, are discussed as promising approaches to improve sleep patterns and support psychological functioning in this population. By integrating neurobiological, clinical and population-level findings, this review highlights the relevance of circadian health in adolescent mental well-being and underscores the importance of chronobiological considerations in preventive and educational strategies.